1965
DOI: 10.1136/hrt.27.3.401
|View full text |Cite
|
Sign up to set email alerts
|

HAeMODYNAMIC EFFECTS OF OXYGEN IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION

Abstract: Oxygen is frequently given in the treatment of patients with acute myocardial infarction. The hemodynamic changes associated with its administration in this condition have not been defined.The purpose of this study has been to investigate the effect of breathing oxygen on the cardiac output and systemic arterial pressure of patients in the early stages of acute myocardial infarction. SUBJECTS AND METHODSSix male patients aged 47 to 72 years were studied on the first and second day of myocardial infarction.In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 11 publications
(13 reference statements)
3
22
0
Order By: Relevance
“…Oxygen therapy was associated with a fall in cardiac output and stroke volume, together with a rise in heart rate. 20 The failing heart requires a higher filling pressure. The higher the filling pressure, the worse the cardiac function; hence an intervention causing a rise in filling pressure is deleterious.…”
Section: Heart Disease and Oxygenmentioning
confidence: 99%
See 3 more Smart Citations
“…Oxygen therapy was associated with a fall in cardiac output and stroke volume, together with a rise in heart rate. 20 The failing heart requires a higher filling pressure. The higher the filling pressure, the worse the cardiac function; hence an intervention causing a rise in filling pressure is deleterious.…”
Section: Heart Disease and Oxygenmentioning
confidence: 99%
“…58 Each item is measured on a Likert-type scale from 0 to 3, and seven non-overlapping items make up each of the two subscales. For each of the two continuous subscales (anxiety and depression), patients are categorised as 'normal' (0-7), 'borderline' (8-10) or 'clinically anxious/depressed' (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Numerical Rating Scale For Breathlessnessmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is also substantive evidence to suggest that high concentration oxygen therapy may be harmful when administered to patients with myocardial ischaemia who are not hypoxaemic [7]. Specifically, high concentration oxygen treatment increases coronary vascular resistance and reduces coronary blood flow [3,[8][9][10][11], increases systemic vascular resistance and blood pressure, and reduces cardiac output [12][13][14][15][16][17][18][19]. The magnitude of these physiological responses may be substantial, as illustrated by a recent systematic review and metaanalysis which reported that high concentration oxygen reduces coronary blood flow by 8 to 29% and increases coronary vascular resistance by 22% to 41% [11].…”
Section: Introductionmentioning
confidence: 96%